Application of Exogenous Ethylene Inhibits Postharvest Peel Browning of ‘Huangguan’ Pear - Ma, Yurong; Yang, Mengnan; Wang, Jingjing; Jiang, Cai-Zhong; Wang, Qingguo (Frontiers in Plant Science, 2017)
Peel browning disorder has an enormous impact on the exterior quality of ‘Huangguan’ pear whereas the underlying mechanism is still unclear. Despite different methods have been applied for inhibiting the peel browning of ‘Huangguan’ pear, there are numerous issues associating with the approaches, such as time-consuming, higher cost, efficacy, safety and the stability of the efficiency. In this study, to develop a rapid, efficient and safe way to protect ‘Huangguan’ pear from skin browning, the effect of exogenous ethylene on peel browning of pear fruits stored at 0℃ was evaluated. Results showed that ethylene treatments at 0.70-1.28 μL/L significantly decreased the browning rate and browning index from 73.80% and 0.30 to 6.80% and 0.02 after 20 days storage at 0℃, respectively, whereas ethylene treatments at 5 μL/L completely inhibited the occurrence of browning. In addition, ethylene treatments at 5 μL/L decreased the electrolyte leakage and respiration rate, delayed the loss of total phenolic compounds. Furthermore, ethylene (5 μL/L) treatment significantly enhanced the activity of catalase (CAT), ascorbate peroxidase (APX) and superoxide dismutase (SOD) and increased the DPPH inhibition rate, whereas inhibited the activity of polyphenol oxidase (PPO) and peroxidase (POD). Our data revealed that ethylene prevented the peel browning through improving antioxidant enzymes (CAT, APX and SOD) activities and reducing the PPO activity, electrolyte leakage rate and respiration rate. This study demonstrated that exogenous ethylene application may provide a safe and effective alternative method for controlling browning and contributed to the understanding of peal browning of ‘Huangguan’ pear.